2021
DOI: 10.1021/acs.iecr.1c04027
|View full text |Cite
|
Sign up to set email alerts
|

ZIFs@chitosan Derived Efficient Bimetallic Carbon-Based Catalyst for Oxygen Reduction

Abstract: The utilization of hydrogen energy is an effective way to alleviate the shortage of traditional energy, carbon emissions, and environmental pollution. As a hydrogen energy conversion device, fuel cells are severely limited by the slow oxygen reduction reaction on the cathode. Herein, we designed and synthesized the composite precursors of ZIF and chitosan, which was used for the preparation of a series of efficient carbon-based catalysts for oxygen reduction by pyrolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…In view of this, an efficient and durable catalyst with a rigid structure, resistant to degradation, is essential for reliable operation. Among metal-free catalysts, defect-rich nitrogen-doped carbon nanotubes (NCNTs) or nanofibers (NCNFs), owing to their robust morphology with modified electronic structure, can offer ORR activity with enhanced durability. Recent investigations have also revealed that the catalytic activity of carbon structures can be enhanced through the encapsulation of metal nanoparticles, leading to the modification of its electronic structure. Thus, the ORR activity of NCNFs can also be increased through the encapsulation of suitable metals such as Fe, Co, etc. However, in all the above cases, the ORR activity of the nonprecious metal-based catalysts has been demonstrated in an alkaline medium with very few reports on the behavior of the catalysts in the acidic medium.…”
Section: Introductionmentioning
confidence: 99%
“…In view of this, an efficient and durable catalyst with a rigid structure, resistant to degradation, is essential for reliable operation. Among metal-free catalysts, defect-rich nitrogen-doped carbon nanotubes (NCNTs) or nanofibers (NCNFs), owing to their robust morphology with modified electronic structure, can offer ORR activity with enhanced durability. Recent investigations have also revealed that the catalytic activity of carbon structures can be enhanced through the encapsulation of metal nanoparticles, leading to the modification of its electronic structure. Thus, the ORR activity of NCNFs can also be increased through the encapsulation of suitable metals such as Fe, Co, etc. However, in all the above cases, the ORR activity of the nonprecious metal-based catalysts has been demonstrated in an alkaline medium with very few reports on the behavior of the catalysts in the acidic medium.…”
Section: Introductionmentioning
confidence: 99%
“…A number of first row transition metal nanoparticle catalysts supported on N-doped carbon (N–C) matrices show good activity and durability for ORR in alkaline media. , Among these, Co-based N–C catalysts show particular promise for practical ORR electrocatalysis. , However, many reported works relating to Co-based N–C catalysts for ORR use expensive precursors or cumbersome methods to prepare carbon materials, such as graphene or carbon nanotubes . While such carbon supports show advantages in laboratory-based studies, they are unfeasible for use in commercial catalysts and ZABs.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, increasingly depleting resources and severe environmental pollution have attracted extensive attention worldwide. To better build a community of shared future for mankind, researchers are committed to developing new renewable and clean energy sources to replace traditional energy sources and mitigate environmental pollution and resource shortage [ 1 , 2 , 3 , 4 , 5 ]. Electrical energy is notable for its clean, efficient, economical, and practical characteristics and has emerged as a pivotal research topic [ 6 ].…”
Section: Introductionmentioning
confidence: 99%